Study the Effect of Cardamom Extracts on Lactobacilli in Comparison to Chlorohexidine gluconate and De-ionized water (in vitro study) - Khalil, Sara I.; Al-Obaidi, Wesal A.; Ali, Wifaq M. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Various herbal extracts are known to provide therapeutic benefits in the oral cavity when used topically. One of these herbs is cardamom which is a dried fruit of the tall permanent herbaceous plant, have its place in the family Zingiberaceae.Objectives: Test the effect of green and black cardamom extracts on Lactobacilli in comparison to chlorhexidine gluconate 0.2% and de-ionized water.Materials and methods: Dried fruits of green and black cardamom were extracted by using alcohol 70% ethanol. Saliva was collected from seven volunteers. Agar well technique with different concentrations of green and black cardamom extracts was used to test the sensitivities of Lactobacilli, as well the effects of both cardamom extracts on viable counts of Lactobacilli.Results: Lactobacilli were sensitive to different concentrations of green and black cardamom extracts starting with (5%) to (40%) using agar well diffusion technique. Both types of cardamom extracts green and black were effective in inhibition of Lactobacilli but still weaker than chlorhexidine gluconate 0.2%. Highly significant reduction in the counts of bacteria were reported with cardamom extracts and chlorhexidine in comparison to neutral control after two hrs..Conclusions: Both types of cardamom (green and black) showed an effect on Lactobacilli but still less than chlorhexidine.